A Regional Genetic Study of Primary Monosymptomatic Nocturnal Enuresis Using Chromosomal Microarray Analysis - YARALI, Oğuzhan; NARALAN, Yüksel Sümeyra (Urology Journal, 2025)
Purpose: This study aimed to investigate the genetic heterogeneity of primary monosymptomatic nocturnal enuresis (PMNE) and assess potential genetic variants contributing to its etiology. Materials and Methods: A total of 92 children aged 5–15 years with a positive family history of PMNE were evaluated. All patients underwent detailed urological and nephrological assessments to exclude organic causes. Genetic testing was performed using high-resolution chromosomal microarray technology to identify potential pathogenic variants. Results: No pathogenic or likely pathogenic copy number variations were identified. A small number of patients exhibited variants of uncertain significance (VUS), none of which were conclusively linked to PMNE after parental segregation analysis. Our findings challenge previous studies that reported significant genetic markers and highlight the complex genetic architecture of PMNE. Conclusion: This study reinforces the genetic heterogeneity of PMNE and suggests it follows a polygenic and multifactorial inheritance pattern. Further research using whole-exome and whole-genome sequencing is needed to explore potential genetic contributors alongside environmental factors.